Study of Information Communication Technology and Economic Growth Performance in Southeast Asian Countries - Ferdy Firmansyah, Muhamad; Ihsaan Rizqulloh, Muhammad; Zulian Maulana, Haikal (Department of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2021)
Information and communication technology is a set of tools or technology which in terminology includes all technical tools for processing and also disclosing informationInformation and communication technology, including media technology, has been growing in the era of globalization. The development of this technology has an impact on changes in people's behavior in the use of mass media and in the end also changes the pattern of effective community development in the digital era as it is today. The development of information and communication technology has brought many changes to human life in the world. Humans are able to penetrate time and space by using technology based on information and communication technology. This study uses secondary data obtained from the World Bank Indocator and the International Telecommunication Union. The method used is a quantitative method with panel data regression from 2010-2019 in eight Southeast Asian countries namely Brunei, Cambodia, Indonesia, Malaysia, Singapore, Philippines, Thailand and Vietnam. The variables used in this study are Economic Growth, ICT Trade Export, ICT Trade Import, Landline Telephone, Mobile Phone, Internet Users, Internet Secure Servers, Fixed Broadband, and Foreign Direct Investment. This study forms three models, namely model 1 for research on Trade Export of ICT, model 2 for research on Trade Import of ICT and model 3 for research on Economic Growth and ICT. The results showed that model 1 found only Fixed Broadband which had a significant influence on ICT exports. In model 2 there are Mobile Phone and Fixed Boradband which have a significant influence on the import of ICT. While in model 3 only Foreign Direct Investment has a significant influence on economic growth.